Changes in consumer behavior in the tourism market caused by the Covid-19 pandemic - Katsitadze, Nana; Kochlamazashvili, Lela; Tushishvili, Natela (Georgian Technical University Publishing House, 2020)
Crisis leads to the creation of new views and demands in consumers. For the sustainable development of destinations, it is important to respond to changes in a timely manner. Therefore, tourism planners need to have predictive information about a new model of consumer behavior formed due to the Covid-19 crisis. Because of the urgency of the issue, the paper studies and analyzes the researches conducted by scholars as well as national and international tourism organizations regarding consumer sentiments and forecast on changes in tourist behavior as a result of Covid-19. A sociological study conducted, conducted, using a sampling survey method, to study the tourism market in Georgia. The study confirmed changes in consumer behavior in the following areas: - As a result of pandemic-induced fears, consumers pay more attention to the level of the healthcare system and the quality of sanitation in destinations and hosting facilities; - Due to the economic crisis they have become more price-sensitive, but not at the expense of comfort and sanitation. - Refusal of mass tourism and travel to crowded destinations. An increased demand for a more Ecofriendly and Sustainable tourism is observed. In addition, a desire of traveling to destinations far from one’s home has revealed, which indicates rapid recovery of international tourism as soon as travel restrictions are lifted.
1. Andrades, L., Dimanche, F., & Ilkevich, S. (2015). Chapter 4: Tourist behaviour and trends In book: Tourism in Russia: A management handbook: Emerald Editors. 2 Bronner, F., & De Hoog, R. (2016). Crisis resistance of tourist demand: The importance of quality of life. Journal of TravelResearch, 55(2), 190–204. 3. Hystad, P. W., & Keller, P. C. (2008). Towards a destination tourism disaster management framework: Long-term lessons from aforest fire disaster. Tourism Management, 29(1),151–162; 4. Katsitadze, N., (2018). State Policy in Tourism – Business (MICE) Tourism in Georgia, “Economics and Business,” vol. XI, #4, pp.127-145; 5. Katsitadze, N., (2018). THE PECULIARITIES OF HOTEL BUSINESS DEVELOPMENT IN NEW TOURISM COUNTRIES: THE CASE OF GEORGIA., International Journal of Business and Management Studies, ISSN: 2158-1479. 5. Katsitadze, N., & Natsvlishvili, I. (2020). The Role of State Regulation and Policy in Tourism Development: The Case of Georgia. Eurasian Economic Perspectives, 13(1), 419-434. 6. Mair, J., Ritchie, B. W., & Walters, G. (2016). Towards a research agenda for post-disaster and post-crisis recovery strategies for tourist destinations: A narrative review. Current Issues in Tourism, 19(1), 1–26. 7. Maslow, A. H. (1943). A theory of human motivation. Psychological Review, 50(4), 370; 8. Nonprobability Sampling. (2008). In L. Given, The SAGE encyclopedia of qualitative research methods: SAGE Publications, Inc.Pegg, S., Patterson, I., & Gariddo, P. V. (2012). 9. Roberts, K. H., Madsen, P., & Desai, V. (2007). Organizational Sensemaking during Crisis. In: Pearson, C.M., Roux-Dufort, C.and Clair, J.A., Eds., International Handbook of Organizational Crisis Management (pp. 109-122). 10. Sönmez, S. F., & Graefe, A. R. (1998). Determining future travel behavior from past travel experience and perceptions of risk and safety. . Journal of Travel Research, 37(2), 171–177. 11. https://www.gnta.ge/ge., 2019 12. https://www.atorus.ru/ratings/analitic_mrch/new/55033.html 13. https://www.unwto.org/tourism-covid-19 14. https://www.oecd.org/coronavirus/en/